PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN PENJUMLAHAN DI KELAS II SDN 02 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Eka Filahanasari; Sonia Yulia Friska; Rita Suryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this research is that there are still many students who think that mathematics is a subject that is difficult to understand and boring. The solution to overcome the problem is by developing a sum board learning media that can help students solve problems regarding addition material and attract students' attention in ongoing learning and determine understanding of the addition concept so that it has an impact on student learning outcomes. This type of research is Research and Development (R&D) research, which uses the ADDIE development model which consists of the analysis stage, the analysis stage includes material analysis, analysis of student needs, and student characteristics. The design stage (design) the design stage is carried out on the summation board media, namely the instrument design, the framework design. The development stage (develop) the development stage is tested for validity. The implementation stage carried out a practicality test, and the evaluation stage carried out an effectiveness test carried out at SD N 02 Sungai Rumbai. The results obtained from the development of the sum board media on fractional material for class II SD N02 Sungai Rumbai students, namely from the results of the validator obtaining an average value of 83% in the very valid category, the practicality value obtained an average value of 91% with the very practical category and the results obtained the effectiveness of obtaining an average value of 90% with a very effective category in improving student learning outcomes. Then the sum board on fractional material obtained from student learning outcomes with a percentage of 90% assessment is included in the very effective category. This media is said because it has an impact on student learning outcomes